The Management Theory Jungle and the Existential Manager - Odiorne, George S. (Academy of Management Journal, 1966)
The article attempts to prove that it is not possible to develop a general theory of management and applies an existential theory of management in the issues in dispute surrounding management theory. The discipline of ontology, which is the science of existence, is used as a framework for organizing the existential manager. Many fields of study such as mathematics and psychology have failed to consider the situational nature of the manager. Similarly, management theory in all its forms has failed to consider situationality. The ontological approach may contribute to the reconstruction of management theory by returning to the core of the subject, reconstructing from the center outward.